Double-Stranded RNA Is Produced by Positive-Strand RNA Viruses and DNA Viruses but Not in Detectable Amounts by Negative-Strand RNA Viruses - Weber, Friedemann (American Society for Microbiology, 2006)
Double-stranded RNA (dsRNA) longer than 30 bp is a key activator of the innate immune response against viral infections. It is widely assumed that the generation of dsRNA during genome replication is a trait shared by all viruses. However, to our knowledge, no study exists in which the production of dsRNA by different viruses is systematically investigated. Here, we investigated the presence and localization of dsRNA in cells infected with a range of viruses, employing a dsRNA-specific antibody for immunofluorescence analysis. Our data revealed that, as predicted, significant amounts of dsRNA can be detected for viruses with a genome consisting of positive-strand RNA, dsRNA, or DNA. Surprisingly, however, no dsRNA signals were detected for negative-strand RNA viruses. Thus, dsRNA is indeed a general feature of most virus groups, but negative-strand RNA viruses appear to be an exception to that rule.